Analysis of the composite material behaviour subjected to dynamic bending using the Hopkinson bar - MASSAQ, Abdellah; RUSINEK, Alexis; KLÓSAK, Maciej; BOULOUZ, Abdellah; KOUTTI, Lahcen (Engineering Transactions, 2016)
The aim of this study is to propose an experimental approach supported by an analytical analysis for polymer materials under dynamic loading. The experimental technique of Hopkinson split pressure bar is used which allows for high impact velocities. The specimens are subjected to the three-point bending and the efficiency of the experimental technique is proved. During quasi-static and dynamic bending tests, the rupture mode is described and the evolution of the energy and the ultimate stresses as a function of the initial impact velocity is discussed. In addition, the critical impact velocity estimated above an important change in the rupture mode is observed. In order to better describe the physical phenomena encountered during the three-point bending impact, the analysis is supported by a rheological model based on a mass-spring system.